Effect of short term starvation on disposition kinetics of chloramphenicol in goats - Abdullah, A. Salam; Baggot, J. D. (Harcourt Publishers Limited, 1986)
The effect of short term starvation on the disposition kinetics of chloramphenicol was determined in goats. The same dosage level (10 mg kg-1) administered intravenously produced higher serum concentrations in the animals when they were starved than when they were not starved. This could be attributed to the significantly smaller (P less than 0.05) volume of the central compartment. Starvation significantly decreased the rate of elimination of chloramphenicol while the apparent volume of distribution of the drug was not altered. A significant decrease in the body clearance, 1.36 +/- 0.95 ml (min kg)-1 in the starved condition compared with 3.78 +/- 2.19 mg (min kg)-1 in the controls, caused a corresponding increase in the half life of chloramphenicol. The decreased rate of elimination was attributed to decreased hepatic microsomal metabolism since starvation did not change the fraction of the dose excreted unchanged in the urine. The clinical significance of the altered disposition of chloramphenicol is that administration at the usual dosing rate would lead to accumulation of the drug and eventual toxicity